Road - Clarke, Alan; Goodyer, John; Ward, John; Armstrong, William; Dudgeon, Neil; Horrocks, Jane (bfi, 2016)
A denser slate of extras can be found on the same disc for Road (1987), a lighter and more profane look at addiction (also made for Screenplay) with alcoholic Scullery (Edward Tudor-Pole) guiding a cast of unemployed characters who address the camera on what amounts to a long pub crawl. Originally intended to be produced on sets, the film was instead moved to real locations with elaborate Steadicam work capturing an intense, raucous air that makes this a major highlight of the set. A young David Thewlis, Jane Horrocks (Absolutely Fabulous), and Lesley Sharp are some of the familiar faces here, all of them excellent, and the use of vintage songs is potent as well with Otis Redding's "Try a Little Tenderness" making a nice climactic centerpiece before "The Commitments" revived it more widely four years later. [mondo-digital.com]
Keywords: DVD-Video